2010
DOI: 10.1091/mbc.e09-05-0437
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-Cytoplasmic Shuttling of Chibby Controls β-Catenin Signaling

Abstract: Chibby (Cby) acts with 14-3-3 to regulate β-catenin localization in the canonical Wnt pathway. We show that Cby harbors functional NLS and NES motifs, and shuttles between the nucleus and cytoplasm. Cby distribution at steady state is controlled by an intricate cooperation between 14-3-3, CRM1 and importin-α, which impacts on β-catenin signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 62 publications
(103 reference statements)
2
68
1
Order By: Relevance
“…Drapper, Chibby, Apc) and by promoting its degradation (e.g. Apc) (Ahmed et al, 1998;Gao et al, 2008;Li et al, 2008Li et al, , 2010. These proteins negatively regulate β-catenin nuclear distribution, while Smp positively regulates it, so it is unlikely that Smp promotes β-catenin nuclear localization through the interaction with these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Drapper, Chibby, Apc) and by promoting its degradation (e.g. Apc) (Ahmed et al, 1998;Gao et al, 2008;Li et al, 2008Li et al, , 2010. These proteins negatively regulate β-catenin nuclear distribution, while Smp positively regulates it, so it is unlikely that Smp promotes β-catenin nuclear localization through the interaction with these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…MBP-and His-tagged recombinant proteins were expressed in Escherichia coli strains BL21 and BL21(DE3) and purified by using amylose beads (New England BioLabs) and Ni-nitrilotriacetic acid (Ni-NTA) His-Bind resin (Novagen), respectively, according to the manufacturers' instructions. MBP pulldown assays were performed as previously described (33,34).…”
Section: Methodsmentioning
confidence: 99%
“…Coimmunoprecipitation (co-IP) assays and immunoblotting were performed as described previously (28,33). Briefly, for co-IP assays, transfected HEK293T cells were harvested in ice-cold lysis buffer (20 mM Tris-HCl [pH 8.0], 135 mM NaCl, 1.5 mM MgCl 2 , 1 mM EGTA, 1% Triton X-100, and 10% glycerol) with a protease inhibitor cocktail (Sigma) and incubated for 20 min on ice with intermit-tent agitation.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting was performed as described previously. 14,17 The primary antibodies used were as follows: rabbit anti-Cby1 13 ; mouse anti-GAPDH (Meridian Life Sciences); mouse anti-E-cadherin (BD Transduction Laboratories); mouse anti-ZO-1 (BD Transduction Laboratories); mouse anti-vimentin (Neomarkers); mouse anti-Flag M2 (Sigma); mouse anti-HA (Proteintech). All HRP-conjugated secondary antibodies were purchased from Jackson ImmunoResearch Laboratories.…”
Section: Co-immunoprecipitation and Western Blot Analysismentioning
confidence: 99%
“…16 We showed that Cby1 contains functional nuclear localization signal (NLS) and nuclear export signal (NES) motifs and constitutively shuttles between the nucleus and cytoplasm. 17 Direct interactions of 14-3-3 proteins with Cby1 facilitate Cby1 binding to CRM1 export receptor, while suppressing Cby1 binding to the nuclear import receptor importin-1a. This results in re-distribution of Cby1 and b-catenin into the cytoplasm, leading to repression of b-catenin target genes.…”
Section: Introductionmentioning
confidence: 99%